Beyond Qawa’id: Developing an Authentic Project-Based Assessment Instrument for Maharatul Kalam in Madrasah Tsanawiyah - Heni Wahyuni; Muhammad Nur Pahlevi; Muhammad Hilla Azka Harlek Putra; Jasnawi Jasnawi; Muhammad Idris Hasibuan; Khotijah Khotijah (Fakultas Tarbiyah dan Keguruan, 2026)
Purpose – This study aims to design and develop a comprehensive video-based project assessment rubric that integrates linguistic performance indicators with digital media quality to evaluate Arabic speaking skills (maharatul kalam) within an authentic learning framework. Design/methods/approach – Employing a Design and Development Research (DDR) approach, the study began with a document analysis of the Grade IX Madrasah Tsanawiyah textbook published by the Kementerian Agama Republik Indonesia, which revealed a significant instructional emphasis on formal grammatical structures at the expense of functional oral communication. To address this gap, a structured rubric was developed based on theories of communicative competence and performance-based assessment, featuring two primary dimensions: Arabic speaking performance (intonation, structure, fluency, and coherence) and video project quality (concept, relevance, and audio-visual synchronization). Findings – Results indicate that the proposed dual-dimensional model provides a theoretically grounded and objective mechanism for teachers to evaluate communicative proficiency, aligning classroom practices with contemporary technology-driven standards. However, the study is limited by its conceptual scope and focus on a specific grade level, necessitating further empirical testing to establish inter-rater reliability. It is recommended that future research explores the scalability of this assessment framework across diverse linguistic domains and educational contexts to foster holistic Arabic language evaluation. Research Implications – The implications of this research suggest that integrating project-based digital tasks can shift the pedagogical focus from rote grammatical recognition to productive language mastery.